Web 2.0 based Intelligent software architecture for photograph sharing - (:unkn) unknown (My University, 2010)
With the development of Web 2.0 technologies, the sharing of photographs has increased. In this paper, the authors evaluate the art of photography, analyze how to develop intelligent photograph sharing system, and explaine the requirements of such systems. The authors present an architecture of an intelligent Web 2.0 based system and in future hope to add more modules for retention of users on the system. The system focuses on Web 2.0 usage, web mining for personalization service, and brings a different approach to collaborative filtering. © Copyright 2010.
Keywords: Client-server architecture; Collaborative filtering; Photograph sharing; Web 2.0; Web mining